Ethnomedicinal documentation, phytochemical characterization, and biological evaluation of the traditional medicinal plants from Swat region of Pakistan - Ajmal Khan; Sujogya Kumar Panda; Haibo Hu; Liliane Schoofs; Walter Luyten (PLoS ONE, 2025)
Traditional medicinal plants are a primary source of natural products which are used for the prevention and treatment of various infections throughout the world. This study documents the ethnomedicinal investigation, phytochemical characterization, thin layer chromatographic (TLC) profiling and bioactivities of 17 traditionally used medicinal plants, belonging to 12 taxonomic families from the Swat region of Pakistan. The plants were collected after interviewing local ethnomedicinal knowledge holders, and confirmation of their effective use by the local population and available literature. The extracts (85) were prepared in five different solvents (hexane, acetone, ethanol, methanol, and water), and were tested for a range of bioactivities: antibacterial (5 Gram-positive and 9 Gram-negative bacteria), antifungal (6 yeasts), antibiofilm (S. aureus and C. albicans), and cytotoxicity (cancerous and non-cancerous cell lines). Results demonstrated that 25% of the extracts showed pronounced activity (inhibition value [IV] > 50%) against different planktonic microbes, and 35% against biofilm strains of bacteria and fungi, with ethanol being the best solvent. Cytotoxicity was often observed against a tumor cell, but rarely against non-tumoral cell lines. A number of phytochemical compounds such as alkaloids, flavonoids, phenols, steroids, terpenoids, coumarins, tannins, saponins, chalcones, and quinones were detected in the extracts using standard phytochemical characterization methods, which were further authenticated through TLC separations. This is the first study to report the phytochemical screening, TLC profiling, and bioactivities of these medicinal plants, particularly their antibiofilm properties, which have not been documented previously by other researchers. This work is a significant addition to the field which reinforces the importance of indigenous knowledge in selecting medicinal plants for drug discovery based on local remedies. In conclusion, plants like Juglans regia, Punica granatum, Artemisia maritima, Aesculus indica, Thymus linearis, Nasturtium officinale, Berberis lyceum, Dysphania ambrosioides, and Mentha spicata show promise for further research as a potential sources for novel drug discovery.